Sodium chloride hydrates provide an archive of ocean fluid freezing rates at icy worlds - Rachael E. Hamp; Mark G. Fox-Powell; Peter Fawdon; Christoph G. Salzmann; Jessica P. Hogan; Milz L. Beaumont; Liam Perera; Stephen P. Thompson (Earth and Planetary Science Letters, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

ACMT Position Statement: Current Evidence Does Not Support Routine Use of Leucovorin for Autism Spectrum Disorder - Maryann Mazer-Amirshahi; Jason R. Siebert; Diane P. Calello; Erin R. Fox; Shan Yin; Andrew Stolbach (Journal of Medical Toxicology, 2026)

Sequence analysis of a viral strain isolated for the first time in the UK, clarifies the identity of a novel species of fabavirus - Naomi Beddoe; Sam McGreig; Adrian Fox; Ian P. Adams; Alec Forsyth (Archives of Virology, 2026)
For the first time sequence data of a fabavirus was identified in dahlia from the UK, which was similar to virus sequence reported from dahlia in China. Initial sequences were determined by high-throughput sequencing (HTS) using the Illumina MiSeq platform, and were verified by Sanger sequencing and 5’ and 3’ rapid amplification of cDNA ends (RACE) polymerase chain reaction (PCR). The genome comprised two RNAs that were 5,851 nucleotide (nt) and 3,468 nt long, excluding the 3’-end poly-A tails, each RNA coded for a single polyprotein. The amino acid (aa) sequence identity percentages shared with recognised Fabavirus members over the protease-polymerase (Pro-Pol), Large Coat Protein (LCP) and combined Coat protein (CP) regions were in range with current demarcation thresholds for a distinct Secoviridae species. These sequence data analyses indicate that the fabavirus sequences identified in dahlia in both China and the UK represent a novel species in the family Secoviridae , genus Fabavirus . The name dahlia fabavirus (DFV) is proposed for this putative novel species tentatively named “ Fabavirus dahliae ”.

Hydrodynamic behavior and design implications in continuous-flow hydrothermal liquefaction systems - Dylan J. Cronin; Juliano Souza dos Passos; Alan H. Zacher; Uriah Kilgore; Andrew J. Schmidt; Samuel P. Fox; Michael R. Thorson (Fuel, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Continental‐wide prioritization of protected areas to address global and habitat‐specific goals for avian biodiversity conservation - Yanjie Xu; Diego Pavón‐Jordán; Tyler Hallman; Tristan R. M. Bakx; Lluís Brotons; Sergi Herrando; Alison Johnston; Brett K. Sandercock; Thomas Sattler; Alaaeldin Soultan; Vitalie Ajder; Dawn E. Balmer; et al. (Conservation Biology, 2026)
The United Nations and European Union have set ambitious conservation goals to halt and reverse declines in biodiversity by protecting 30% of land and sea areas by 2030. Effective conservation planning requires evidence‐based spatial prioritization to maximize the coverage of species within designated protected areas. Based on a pan‐European database for occurrence and abundance of breeding birds collected in the 2010s, we applied the Zonation algorithm to identify key areas that would maximize the protection of ranges and populations for 435 species of breeding birds across Europe using either continental or national prioritization targets. When 30% of Europe's highest priority terrestrial areas were selected by the algorithm, 49% of species’ ranges and 63% of species’ populations were protected. When 10% and 30% of the highest priority lands were selected, compared with prioritization using occurrence data, prioritization using abundance data resulted in a higher percentage of species’ populations, especially rare and range‐restricted species, being represented for protected area coverage. Stratifying prioritization by habitat criteria greatly enhanced habitat‐specific conservation efficiency, enabling coverage of over 80% of breeding bird species’ populations in tundra, Mediterranean, and coastal habitats with a selection of 10% of the highest priority areas for each. Our prioritization supports international targets adopted under the Kunming–Montreal Global Biodiversity Framework by identifying key areas and providing a roadmap to guide optimal site protection and conservation planning in Europe.

Expanding insights into plant rhabdovirus diversity through the discovery of viruses representing 32 putative novel species - Marleen Botermans; P. P. M. de Koning; M. Westenberg; I. P. Adams; K. Ben Mansour; C. Chabi-Jesus; C. de Krom; A. M. Dullemans; R. Festus; A. R. Fowkes; A. Fox; J. Freitas-Astúa; et al. (Archives of Virology, 2026)
Plant-infecting rhabdoviruses (family Rhabdoviridae , subfamily Betarhabdovirinae ) include several viruses that cause important crop diseases and are subject to phytosanitary regulation. Despite their agricultural and ecological importance, the diversity of plant rhabdoviruses and their impact on plant health remain poorly understood. Here, we report 32 tentative novel species of plant-infecting rhabdoviruses, identified via high-throughput sequencing and spanning nine established genera. The virus sequences originated from diverse hosts and geographic regions, revealing extensive diversity within the family Rhabdoviridae . Several viruses were detected independently in the same host species across multiple countries, demonstrating the practical value of data sharing for confirming host associations and gaining insight into the geographic distribution of these viruses. Our study highlights the underexplored diversity of plant rhabdoviruses and demonstrates the value of coordinated, collaborative virus discovery. With HTS now widely accessible, the challenge has shifted from virus discovery to making sequence data and metadata publicly available, and to conducting the time-consuming biological characterization often deprioritized in favour of viruses with immediate phytosanitary relevance. As a result, many findings remain unreported, leaving valuable data dormant on servers. By sharing genomic data prior to publication, we present an efficient approach to accelerate virus reporting, enable comparative analyses and advance understanding of virus diversity. We hope this collaborative effort will encourage further exploration of plant viruses, including those from hosts without discernable symptoms, supporting virus biology, taxonomy, pest risk assessments, and plant health policies.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Initiation of dolutegravir vs. efavirenz on 12- and 24-month retention and viral suppression: a target trial emulation - Amy Zheng; Alana T. Brennan; Ross Greener; Emma M. Kileel; Jacob Bor; Willem D. F. Venter; Eleanor J. Murray; Pedro T. Pisa; Bridgette Goeieman; Matthew P. Fox; Mhairi Maskew (Infectious Diseases, 2026)

Highly engaged marine users can help monitor marine plastic pollution in under accessed environments - Peter S. Puskic; Isabelle Cramer; Emma Church; Emily Deery; Matthias Egger; Natalie Fox; William P. de Haan; Laurent Lebreton; Arianna Liconti; Anna Sanchez-Vidal; Helen Wolter (Ocean & Coastal Management, 2026)

Stable Isotope Ecology of the Early Miocene Rusinga Island Mammalian Communities from the Hiwegi and Kulu Formations (Nyanza Province, Western Kenya) - David L. Fox; Nicole D. Garrett; Daniel J. Peppe; Lauren A. Michel; Kirsten Jenkins; Thomas Lehmann; Kieran P. McNulty (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Evaluation of the WEPS hydrology sub-model for surface soil water content under different tillage practices in the inland Pacific Northwest, USA - Huawei Pi; David R. Huggins; Larry.E. Wagner; Fred. Fox; Sisi Li; Nicholas P. Webb (CATENA, 2025)

Genomic Characterization Reveals Infections and Silent Dissemination of Carbapenemase-Producing Klebsiella Oxytoca Complex Associated with ST2 Lineage in a Hospital Setting - Verónica E. Álvarez; Camila Knecht; María Piekar; Natalia García Allende; Adrián Gonzales Machuca; Josefina Campos; Eduardo Carpio; Laura Páez; Bárbara Fox; Liliana Fernández Canigia; Carolina Leguina; María P. Quiroga; et al. (Current Microbiology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Exposure to airborne polychlorinated biphenyls and risk of uterine leiomyomata, endometriosis, and polycystic ovarian syndrome: A register-based Danish cohort study - Sandra Søgaard Tøttenborg; Lauren Anne Wise; Amelia Kent Wesselink; Henriette Svarre Nielsen; Kajsa Ugelvig Petersen; Matthew P. Fox; Marie Frederiksen; Esben Meulengracht Flachs; Harald William Meyer; Karin Sørig Hougaard; Jens Peter Bonde; Laura Deen (Environmental Toxicology and Pharmacology, 2025)

Bioconcentration and toxicity of perfluoroalkyl substances (PFAS) in embryonic stages of the ecologically and commercially relevant Olive Flounder (Paralichthys olivaceus), and the zebrafish (Danio rerio) embryo model system - Kiflom Gebreab; Ariel Lawson; Giancarlos Garcia; Jessica Fox; Daniel Benetti; John D. Stieglitz; Natalia Soares Quinete; John P. Berry (Ecotoxicology, 2025)

Abiotic environmental factors contribute to spatial variation in boldness and exploration in guppies ( Poecilia reticulata ) - Alexis M. Heckley; Pierre‐Olivier Montiglio; Janay A. Fox; Sarah Sanderson; Alison M. Derry; Kiyoko M. Gotanda; Andrew P. Hendry (Journal of Fish Biology, 2025)
Research on wild fishes has tended to overlook the role of abiotic factors in shaping behaviours associated with boldness and exploration. This oversight could exist because small‐scale variation in the abiotic environment might seem unlikely to influence such behaviours. We challenged this assumption through research in the Trinidadian guppy ( Poecilia reticulata ) system. We started by quantifying how behaviours associated with boldness (time in a shelter and time frozen in an open field) and a behaviour associated with exploration (number of grid squares crossed in an open field) varied for guppies within and among 15 pools across two streams, where all of the pools within a stream were within 150 m of each other. The measured behaviours differed little between streams, yet they varied dramatically among pools within streams and among individuals within pools, thus illustrating how such behaviours can be structured on very small spatial scales. We next assessed how the observed behavioural variation might be explained by individual‐level attributes (sex and body mass) and pool‐level abiotic factors (e.g. temperature and dissolved oxygen). Individual‐level attributes explained little of the behavioural variation, although smaller guppies did display slightly bolder behaviour. Among‐pool abiotic factors, however, were quite informative. As a clear example, guppies from pools with less dissolved oxygen displayed bolder behaviour and (possibly) greater exploration. Our results highlight the importance of abiotic factors in shaping behaviour even on small spatial scales.

Measuring the social impact of City-region food system initiatives (CRFSIs): A systematic review of indicators and metrics - K. Specht; C. Iodice; F. Monticone; P. Tonini; M. Petruzzelli; L. Carotti; R. Fox-Kämper; S. Toboso-Chavero; F. Orsini; A. Samoggia; M. Vittuari (Sustainable Cities and Society, 2025)

The effects of handling on stress response markers in a reef fish model for aquaculture development, the brassy chub, Kyphosus vaigiensis - Reilly S. Merlo; Bradley K. Fox; Andre P. Seale (Journal of Fish Biology, 2025)
With the expanding global population, interest has increased in the sustainable aquaculture development of indigenous fishes. In Hawaiʻi, the brassy chub, Kyphosus vaigiensis , has drawn interest as a candidate species for production. However, little is known about its resilience in aquaculture settings where fish are exposed to acute, husbandry‐related stressors. To address the response of brassy chub to handling stress, we characterized the effects of simulated netting and confinement stress on physiological parameters indicative of the alarm and resistance phases of the stress response over a 24‐h time course. Specifically, we measured plasma osmolality and glucose, mucous cortisol, hepatic activity of the antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPX), and hepatic lipid peroxidation (LPO). Plasma osmolality in stressed fish was increased relative to controls at 1 and 6 h. Mucous cortisol levels were transiently increased in stressed fish at 1 h following handling stress. In stressed fish, plasma glucose was generally increased from 1 h to 24 h relative to controls. By contrast, SOD activity decreased in stressed fish at 6 and 12 h, returning to control levels at 24 h; GPX activity and LPO were unaffected by the handling stressor. The transient and modest responses of mucous cortisol and antioxidant enzyme activity indicate the recovery of brassy chub from handling stress. Moreover, the sustained increase in plasma glucose and lack of change in LPO suggest mobilization of energy and long‐term resiliency toward handling stressors.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Nutritional monitoring of rangeland beef cattle in the Edwards Plateau of Texas using region-specific fecal near-infrared spectroscopy predictions of diet quality - Douglas R. Tolleson; William E. Fox; William E. Pinchak; Jay P. Angerer (Rangelands, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Six decades of global coral bleaching monitoring: a review of methods and call for enhanced standardization and coordination - Andrea Rivera-Sosa; Aarón Israel Muñiz-Castillo; Ben Charo; Gregory P. Asner; Chris M. Roelfsema; Simon D. Donner; Brianna D. Bambic; Ana Gabriela Bonelli; Morgan Pomeroy; Derek Manzello; Paulina Martin; Helen E. Fox (Frontiers in Marine Science, 2025)
Coral bleaching poses a severe threat to the health and survival of global coral reef ecosystems, with recent events surpassing historical heat stress records. To address this crisis, improved long-term monitoring, communication, and coordination are urgently required to enhance conservation, management, and policy responses. This study reviews global coral bleaching survey methodologies and datasets spanning 1963 to 2022, identifying key challenges in methodological standardization, including database duplication and inconsistencies in naming and reporting bleaching metrics. These issues hinder comparative analyses and contribute to discrepancies in global bleaching impact assessments. We developed a typology of twenty-nine coral bleaching methods used across various scales, encompassing remote sensing tools, underwater surveys, and specimen collection. Analysis of 77,370 observations from three major datasets revealed that 9.36% of entries lacked methodological descriptions. Among recorded methods, belt transects (42%), line and point intercept transects (33%), and random surveys (17%) were the most widely applied. Practitioner surveys underscored the dominance of in situ transect and visual methods, highlighting the growing adoption of photo quadrats—an emerging yet underrepresented technique in existing datasets. To enhance global coral bleaching assessments, we propose a standardized framework that ensures open access and accessible data that aligns with decision-makers’ needs for efficient data aggregation and interoperability to better understand temporal and spatial bleaching events. A globally coordinated coalition should unify protocols, improve data-sharing capabilities, and empower regional networks through targeted training, incentives, and open communication channels. Strengthening field capacity in coral taxonomy and standardized survey methodologies, alongside integrating advanced tools, will improve data quality and comparability. Additionally, creating precise geolocated datasets will bridge on-the-ground observations with advanced remote sensing systems, refining the accuracy of satellite-based early warning tools. Establishing interoperable online platforms will further streamline data integration and accessibility, providing a robust foundation to support global responses to coral bleaching and foster impactful conservation initiatives.

Tracking the geographical distribution of the Asian citrus psyllid Diaphorina citri throughout China using mitogenomes and endosymbionts - Fengnian Wu; Zehan Dai; Min Shi; Jianjian Huang; Hui Zhu; Yuzhong Zheng; Zikai Chen; Xiuhong Li; Xiaoling Deng; Eduardo G. P. Fox (Journal of Pest Science, 2025)

Correction to: Prioritizing Opportunities to Empower Forest Carbon Decisions Through Strategic Investment in Forest Modeling Capacity - Christopher W. Woodall; Holly L. Munro; Jeff W. Atkins; Bronson P. Bullock; Thomas R. Fox; Coeli M. Hoover; Stephen M. Kinane; Lara T. Murray; Stephen P. Prisley; John D. Shaw; Erin Smith-Mateja; Aaron R. Weiskittel; et al. (Journal of Forestry, 2025)

Prioritizing Opportunities to Empower Forest Carbon Decisions Through Strategic Investment in Forest Modeling Capacity - Christopher W. Woodall; Holly L. Munro; Jeff W. Atkins; Bronson P. Bullock; Thomas R. Fox; Coeli M. Hoover; Stephen M. Kinane; Lara T. Murray; Stephen P. Prisley; John D. Shaw; Erin Smith-Mateja; Aaron R. Weiskittel; et al. (Journal of Forestry, 2025)

Socioecological drivers of injuries and aggression in female and male rhesus macaques (Macaca mulatta) - Melissa A. Pavez-Fox; Erin R. Siracusa; Samuel Ellis; Clare M. Kimock; Nahiri Rivera-Barreto; Josue E. Negron-Del Valle; Daniel Phillips; Angelina Ruiz-Lambides; Noah Snyder-Mackler; James P. Higham; Delphine De Moor; Lauren J. N. Brent (Behavioral Ecology and Sociobiology, 2025)
Competition over access to resources, such as food and mates, is one of the major costs associated with group living. Two socioecological factors believed to drive the intensity of competition are group size and sex ratio. However, empirical evidence linking these factors to physical aggression and injuries is scarce. Here, we leveraged 10 years of data from free-ranging female and male rhesus macaques to test whether group size and adult sex ratio predicted the risk of inter and intrasexual aggression, as well as injury risk. We found evidence for an optimal group size at which the risk of intragroup aggression was minimized for both sexes. Despite male-male aggression being lowest in mid-sized groups, males in smaller groups experienced higher injury risk, suggesting within-group aggression might not be the main cause of male injury. Additionally, we found that sex ratio influenced aggression, but not injury risk. Specifically, female aggression toward other females was heightened during the birth season when groups had fewer available males, suggesting either female competition for male friends or exacerbated female-female competition due to the energetic costs of lactation. Male aggression towards females was higher in female-biased groups during the birth season and in male-biased groups during the mating season, which could reflect male competition with females over feeding opportunities and male coercion of females, respectively. Together, these findings provide insights into fitness costs (i.e., injury risk) of inter and intrasexual competition in primates in relation to key aspects of social organization. Significance statement While theory suggests that group size and sex ratio influence competition, studies linking these factors to aggression and injury rates are limited. Using long-term data on demography, aggression, and injury from a group-living primate, we show that both males and females experience aggression less often at intermediate group sizes. However, males in smaller groups faced higher injury risks. Although sex ratio did not predict injury risk, it did influence intra- and intersexual aggression, with patterns varying by reproductive season. Overall, our findings provide insights into how competition shapes intra and intersexual dynamics in relation to aspects of social organization.

Breeding waterbird species as ecological indicators of shifts from turbid to clear water conditions in northwest European shallow eutrophic lakes - Anthony D. Fox; Hans E. Jørgensen; Erik Jeppesen; Torben L. Lauridsen; Martin Søndergaard; Karsten Fugl; Palle P. Myssen; Thorsten J. S. Balsby; Preben Clausen; Petr Musil; Zuzana Musilová (Hydrobiologia, 2025)
We used biological and physical responses at 71 shallow waterbodies with contrasting nutrient levels undergoing recovery from eutrophication to predict potential changes in waterbird species abundance, an important component of lake ecosystems. These general predictions were tested using 28 years of breeding waterbird data from three Danish shallow eutrophic lakes, comparing species-specific responses to improved nutrient and water transparency in two lakes with a third where conditions remained constantly suitable for breeding waterbirds. We predicted positive responses to improved water quality from pursuit diving predators (three grebe species), a specialist zooplankton feeder (northern shoveler Anas clypeata ) and waterbirds feeding on (common pochard Aythya ferina ) or within (tufted duck A. fuligula ) submerged macrophyte underwater canopies. These species were characterised by positive waterbird community composition changes (using Principal Components Analysis) associated with decreasing nutrient loading and increasing water transparency at two lakes, with no change in breeding waterbird community at the third. Secchi depth explained 73–95% of variance in both PC axes at both restored lakes, but not at the third, suggesting water transparency was the major factor driving waterbird community composition. These examples show predicting waterbird species-specific responses to management can usefully direct the use of breeding waterbirds as indicator species.

A review of the venom microbiome and its utility in ecology and evolution including future directions for emerging research - Marina E. De León; Eduardo G. P. Fox; Sara Dunaj; Ronald A. Jenner; Carl N. Keiser; Jason Macrander; Samantha A. Nixon; Clarissa J. Nobile; Daniel Petras; Eduardo Rodriguez-Roman; Anthony J. Saviola; Steven A. Trim; et al. (Symbiosis, 2025)

Cooperation by harvester ant queens brings direct energetic benefits during colony founding - Rebecca M. Clark; Trevor P. Fox; Jennifer H. Fewell; Jon F. Harrison (Behavioral Ecology and Sociobiology, 2025)
Cooperative behavior by nonrelatives is an evolutionary puzzle, because costs of cooperation are often strong while selective factors favoring cooperative groups remain unclear. In some populations of the seed harvester ant P ogonomyrmex californicus , unrelated queens form groups at colony founding (pleometrosis), whereas in other populations, colonies are initiated by single queens (haplometrosis). We tested the hypothesis that energetic savings of grouping contribute a benefit that may enhance queen success during colony founding and early growth for pleometrotic colonies. We measured metabolic rates and locomotor activity of individuals or pairs of freshly collected, newly mated P. californicus queens from pleometrotic and haplometrotic populations. Population source did not significantly affect metabolic rates, but paired queens from both populations had mass-specific metabolic rates only 86% of those of individual queens. The metabolic effect of grouping was not explained by differences in locomotion. To test whether this degree of energetic saving could be biologically significant, we assessed metabolic rate, body mass, and egg production for pleometrotic pairs at four time points of colony founding and compared the energetic content of stored lipid to energy use up to the point of worker emergence. Metabolic rates dropped over time for queens, as did body mass, and gas exchange switched from continuous to discontinuous, suggestive of metabolic suppression. Total joules required for queens to reach the worker emergence stage were 1.5 times the energy content of stored lipids, consistent with the need for foraging for these queens, and supporting the hypothesis that energetic savings of grouping can be beneficial by extending energetic stores and reducing the need for risky foraging.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Drivers of moth phenology in England and Wales - Emily J. Hickinbotham; Zarah Pattison; Richard Fox; Steve P. Rushton (Journal of Insect Conservation, 2024)
Climate change has led to changes in the phenology of Lepidoptera species. While phenological shifts have been previously measured for moth species in England and Wales, the drivers of these shifts are not well known. Here, we use data from the National Moth Recording Scheme and the Garden Moth Scheme to investigate the drivers of phenology in 149 moth species over a 50 year period from 1970 to 2019. We investigate whether there have been phenological shifts in adult emergence using three phenology metrics: First Emergence (FE), Peak Emergence (PE), and Emergence Standard Deviation (ESD) in relation to life history traits and temperature. Overwintering stage had a significant impact on moth phenology, so we analysed species that spend the winter as eggs, larvae or pupae separately. Overall phenological changes were different depending on overwintering stage category and phenological measure, with the rate of phenological shifts increasing with later overwintering life stages in response to both temperature and year. The overwintering stage larva was the only one impacted by diet, with those that feed on woody hostplants emerging ~ 17 days later than species with herbaceous hostplants. These results indicate that species that either overwinter in earlier life stages or have woody hostplants may be less adaptable to climate change, and thus should be the targets of conservation efforts.

First report of carnation Italian ringspot virus in Gypsophila in the United Kingdom - G. Webster; L. Frew; R. Ward; A. R. Fowkes; A. Skelton; V. Harju; I. P. Adams; S. McGreig; H. Pufal; C. Conyers; A. Fox (Journal of Plant Pathology, 2024)

Coding genome of a novel potyvirus, hogweed virus Y (HogVY) - Daisy Furrokh; Sam McGreig; Ian P. Adams; Ben Barrett; Aimee Fowkes; Anna Skelton; Adrian Fox; Ines Vazquez-Iglesias (Journal of Plant Pathology, 2024)

Counter‐gradient variation in gene expression between fish populations facilitates colonization of low‐dissolved oxygen environments - Janay A. Fox; David A. G. A. Hunt; Andrew P. Hendry; Lauren J. Chapman; Rowan D. H. Barrett (Molecular Ecology, 2024)
The role of phenotypic plasticity during colonization remains unclear due to the shifting importance of plasticity across timescales. In the early stages of colonization, plasticity can facilitate persistence in a novel environment; but over evolutionary time, processes such as genetic assimilation may reduce variation in plastic traits such that species with a longer evolutionary history in an environment can show lower levels of plasticity than recent invaders. Therefore, comparing species in the early stages of colonization to long‐established species provides a powerful approach for uncovering the role of phenotypic plasticity during different stages of colonization. We compared gene expression between low‐dissolved oxygen (DO) and high‐DO populations of two cyprinid fish: Enteromius apleurogramma , a species that has undergone a recent range expansion, and E. neumayeri , a long‐established native species in the same region. We sampled tissue either immediately after capture from the field or after a 2‐week acclimation under high‐DO conditions, allowing us to test for both evolved and plastic differences in low‐DO vs high‐DO populations of each species. We found that most genes showing candidate‐evolved differences in gene expression did not overlap with those showing plastic differences in gene expression. However, in the genes that did overlap, there was counter‐gradient variation such that plastic and evolved gene expression responses were in opposite directions in both species. Additionally, E. apleurogramma had higher levels of plasticity and evolved divergence in gene expression between field populations. We suggest that the higher level of plasticity and counter‐gradient variation may have allowed rapid genetic adaptation in E. apleurogramma and facilitated colonization. This study shows how counter‐gradient variation may impact the colonization of divergent oxygen environments.

A novel virus of the family Secoviridae detected in lettuce in the United Kingdom and in dandelion in Slovakia - Ian P. Adams; Giuseppe Micali; Ummey Hany; Anna Skelton; Val Harju; Adam Buxton-Kirk; Lukáš Predajňa; Katarína Šoltys; Michaela Mrkvová; Miroslav Glasa; Adrian Fox (Journal of Plant Pathology, 2024)

Trade-offs between sociality and gastrointestinal parasite infection in the context of a natural disaster - Melissa A. Pavez-Fox; Carla M. Escabi-Ruiz; Jordan D.A. Hart; Josue E. Negron-Del Valle; Daniel Phillips; Angelina Ruiz-Lambides; Samuel E. Bauman; Melween I. Martinez; Michael J. Montague; Michael L. Platt; James P. Higham; Noah Snyder-Mackler; et al. (Animal Behaviour, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Cohesion and shear strength of compacted lunar and Martian regolith simulants - B. Dotson; D. Sanchez Valencia; C. Millwater; P. Easter; J. Long-Fox; D. Britt; P. Metzger (Icarus, 2024)

Genomic Characterization of Two NDM-5-Producing Isolates of Klebsiella pneumoniae ST11 from a Single Patient - Verónica E. Álvarez; Laura Carrera Páez; María Piekar; Natalia García Allende; Josefina Campos; Nicolás Mendiondo; Andrea Aguilar; Barbara Fox; Liliana Fernández-Canigia; María P. Quiroga; Daniela Centrón (Current Microbiology, 2024)

Validation of a molecular sex marker in three sturgeons from eastern North America - Nicholas M. Sard; Brian R. Kreiser; Richard M. Pendleton; Barbara A. Lubinski; Robin L. Johnson; Dewayne A. Fox; Joel P Van Eenennaam; Jason E. Kahn; Chris Hager; Amanda L. Higgs; David C. Kazyak (Conservation Genetics Resources, 2024)

Michael F. Tillman 1943–2023 - Robert L. Brownell; Linda L. Jones; Douglas P. DeMaster; Greg P. Donovan; Stephen B. Reilly; Rolland A. Schmitten; Jeffrey M. Breiwick; Robert Suydam; Daryl J. Boness; William W. Fox (Marine Mammal Science, 2024)

Nerine potexvirus 1: a new Potexvirus species detected from Nerine in the United Kingdom - Naomi Beddoe; Sam McGreig; John Walsh; Adrian Fox; Ian P. Adams; Alec Forsyth (Journal of Plant Pathology, 2023)

Immune cell composition varies by age, sex and exposure to social adversity in free-ranging Rhesus Macaques - Mitchell R. Sanchez Rosado; Nicole Marzan-Rivera; Marina M. Watowich; Andrea D. Negron-Del Valle; Petraleigh Pantoja; Melissa A. Pavez-Fox; Erin R. Siracusa; Eve B. Cooper; Josue E. Negron-Del Valle; Daniel Phillips; Angelina Ruiz-Lambides; Melween I. Martinez; et al. (GeroScience, 2023)

Wet air oxidation of HTL aqueous waste - Uriah J. Kilgore; Senthil Subramaniam; Samuel P. Fox; Dylan J. Cronin; Mond F. Guo; Andrew J. Schmidt; Karthikeyan K. Ramasamy; Michael R. Thorson (Biomass and Bioenergy, 2023)

Physicochemical and immunological effects of adjuvant formulations with snake venom antigens for immunization of horses for antivenom production - Christopher B. Fox; Amit P. Khandhar; Lisa Khuu; Tony Phan; Robert Kinsey; Daniel Cordero; José María Gutiérrez; Guillermo León (Toxicon, 2023)

Co-alteration Network Architecture of Major Depressive Disorder: A Multi-modal Neuroimaging Assessment of Large-scale Disease Effects - Jodie P. Gray; Jordi Manuello; Aaron F. Alexander-Bloch; Cassandra Leonardo; Crystal Franklin; Ki Sueng Choi; Franco Cauda; Tommaso Costa; John Blangero; David C. Glahn; Helen S. Mayberg; Peter T. Fox (Neuroinformatics, 2023)

Meta-analytic connectivity modelling of functional magnetic resonance imaging studies in autism spectrum disorders - Alicia M. Goodwill; Li Tong Low; Peter T. Fox; P. Mickle Fox; Kenneth K. Poon; Sourav S. Bhowmick; S. H. Annabel Chen (Brain Imaging and Behavior, 2023)
Social and non-social deficits in autism spectrum disorders (ASD) persist into adulthood and may share common regions of aberrant neural activations. The current meta-analysis investigated activation differences between ASD and neurotypical controls irrespective of task type. Activation likelihood estimation meta-analyses were performed to examine consistent hypo-activated and/or hyper-activated regions for all tasks combined, and for social and non-social tasks separately; meta-analytic connectivity modelling and behavioral/paradigm analyses were performed to examine co-activated regions and associated behaviors. One hundred studies (mean age range = 18–41 years) were included. For all tasks combined, the ASD group showed significant (p < .05) hypo-activation in one cluster around the left amygdala (peak − 26, -2, -20, volume = 1336 mm 3 , maximum ALE = 0.0327), and this cluster co-activated with two other clusters around the right cerebellum (peak 42, -56, -22, volume = 2560mm 3 , maximum ALE = 0.049) Lobule VI/Crus I and the left fusiform gyrus (BA47) (peak − 42, -46, -18, volume = 1616 mm 3 , maximum ALE = 0.046) and left cerebellum (peak − 42, -58, -20, volume = 1616mm 3 , maximum ALE = 0.033) Lobule VI/Crus I. While the left amygdala was associated with negative emotion (fear) (z = 3.047), the left fusiform gyrus/cerebellum Lobule VI/Crus I cluster was associated with language semantics (z = 3.724) and action observation (z = 3.077). These findings highlight the left amygdala as a region consistently hypo-activated in ASD and suggest the potential involvement of fusiform gyrus and cerebellum in social cognition in ASD. Future research should further elucidate if and how amygdala-fusiform/cerebellar connectivity relates to social and non-social cognition in adults with ASD.

Observations of Multiple Young-of-the-Year to Juvenile White Sharks (Carcharodon carcharias) within South-West Australian Waters and Its Implications for a Potential Nursery Area(s) - Craig P. O’Connell; Marc Payne; Shelley Payne; Luke J. Eller; Jon Shaw; Andrew McGregor; Andre Rerekura; Madison Stewart; Andrew Fox (Journal of Marine Science and Engineering, 2023)
The white shark (Carcharodon carcharias) is a globally distributed top predator. Due to its ecological importance, increasing knowledge through continued research can enhance management measures. One such facet of biological knowledge is the identification of shark nursery areas, as protection of these regions is critical to species survival. Presently, there are two known C. carcharias nursery areas in association with the Eastern Australian subpopulation; however, a nursery area associated with the Southern-Western Australian C. carcharias subpopulation has yet to be identified. Herein, we report opportunistic laser photogrammetry, stereo-photogrammetry, and baited remote underwater video systems (BRUVS) data that resulted in the identification of sixteen young-of-the-year (YOY)-juvenile C. carcharias from two separate regions (i.e., Salisbury Island and Daw Island) in South-West Australia. Additionally, anecdotal bycatch data associated with two YOY C. carcharias (i.e., 1.40 and 1.70 m total length) from another location within the Great Australian Bight are reported. While it is premature to conclude that these sites represent discrete or an expansive interconnected nursery area, the sightings success in this study is indicative that future research may want to consider implementing a study during a similar time period (i.e., February–March) while using a similar attractant methodology (i.e., bottom-set BRUVS baited with squid [Sepioteuthis australis]) to help elucidate the unique life-history characteristics of this C. carcharias subpopulation.

Compound-specific carbon isotope evidence that the initial carbon isotope excursion in the end-Triassic strata in northwest Tethys is not the product of CAMP magmatism - Sarah J. Beith; Calum P. Fox; John E.A. Marshall; Jessica H. Whiteside (Global and Planetary Change, 2023)

Long-term aircraft noise exposure and risk of hypertension in postmenopausal women - Daniel D. Nguyen; Eric A. Whitsel; Gregory A. Wellenius; Jonathan I. Levy; Jessica H. Leibler; Stephanie T. Grady; James D. Stewart; Matthew P. Fox; Jason M. Collins; Melissa N. Eliot; Andrew Malwitz; JoAnn E. Manson; et al. (Environmental Research, 2023)

Characteristics of extreme daily precipitation events over the Canadian Arctic - Mark C. Serreze; Jessica Voveris; Andrew P. Barrett; Shari Fox; Peter D. Blanken; Alex Crawford (International Journal of Climatology, 2022)
Given growing interest in extreme high‐latitude weather events, we use records from nine meteorological stations and atmospheric reanalysis data to examine extreme daily precipitation events (leading, 99th and 95th percentile) over Arctic Canada. Leading events span 90 mm at Cape Dyer, along the southeast coast of Baffin Island, to 26 mm at Sachs Harbour, on the southwest coast of Banks Island. The 95th percentiles range from 20 to 30% of leading event sizes. Extreme events are most common on or near the month of climatological peak precipitation. Contrasting with Eurasian continental sites having a July precipitation peak corresponding to the seasonal peak in precipitable water, seasonal cycles in precipitation and the frequency of extremes over Arctic Canada are more varied, reflecting marine influences. At Cape Dyer and Clyde River, mean precipitation and the frequency of extremes peak in October when the atmosphere is quickly cooling, promoting strong evaporation from Baffin Bay. At all stations, leading events involved snowfall and strong winds and were associated with cyclone passages (mostly of relatively strong storms). They also involved strong vapour fluxes, sometimes associated with atmospheric rivers or their remnants. The most unusual sequence of events identified here occurred at Clyde River, where the three largest recorded precipitation events occurred in April of 1977. Obtaining first‐hand accounts of this series of events has proven elusive. Identified links between extreme events and atmospheric rivers demonstrates the need to better understand how the characteristics of such features will change in the future.

Global patterns of illegal marine turtle exploitation - Jesse F. Senko; Kayla M. Burgher; Maria del Mar Mancha‐Cisneros; Brendan J. Godley; Irene Kinan‐Kelly; Trevor Fox; Frances Humber; Volker Koch; Andrew T. Smith; Bryan P. Wallace (Global Change Biology, 2022)
Human exploitation of wildlife for food, medicine, curios, aphrodisiacs, and spiritual artifacts represents a mounting 21st‐century conservation challenge. Here, we provide the first global assessment of illegal marine turtle exploitation across multiple spatial scales (i.e., Regional Management Units [RMUs] and countries) by collating data from peer‐reviewed studies, grey literature, archived media reports, and online questionnaires of in‐country experts spanning the past three decades. Based on available information, we estimate that over 1.1 million marine turtles were exploited between 1990 and 2020 against existing laws prohibiting their use in 65 countries or territories and in 44 of the world's 58 marine turtle RMUs, with over 44,000 turtles exploited annually over the past decade. Exploitation across the 30‐year period primarily consisted of green (56%) and hawksbill (39%) turtles when identified by species, with hawksbills (67%) and greens (81%) comprising the majority of turtles exploited in the 1990s and 2000s, respectively, and both species accounting for similar levels of exploitation in the 2010s. Although there were no clear overarching trends in the magnitude or spatial patterns of exploitation across the three decades, there was a 28% decrease in reported exploitation from the 2000s to the 2010s. The 10 RMUs with the highest exploitation in the 2010s included seven green and three hawksbill turtle RMUs, with most reported exploitation occurring in RMUs that typically exhibit a low risk of population decline or loss of genetic diversity. Over the past decade, the number of RMUs with “moderate” or “high” exploitation impact scores decreased. Our assessment suggests that illegal exploitation appears to have declined over the past decade and, with some exceptions, is primarily occurring in large, stable, and genetically diverse marine turtle populations.

Comparisons between sequenced and re-sequenced genomes of historical subterranean clover mottle virus isolates - John Fosu-Nyarko; Ian P. Adams; Michael G. K. Jones; Adrian Fox; Roger A. C. Jones (Journal of Plant Pathology, 2022)
We report comparisons between the complete genomic sequences of five historical Western Australian isolates of subterranean clover mottle virus (SCMoV) from 1989–2000, and an infectious clone of its 1989 isolate. Sanger Sequencing (SS) and High Throughput Sequencing (HTS), or both, were used to obtain these genomes. Four of the SCMoV isolates were sequenced by SS in 1999–2002, but re-sequenced again by HTS in 2020. The pairs of sequences obtained from these four isolates differed by only 18–59 nucleotides. This small difference resulted from the different sequencing methods, the < 1–5 years each isolate was host passaged before freeze-drying prior to HTS sequencing, or a combination of both. Since SCMoV has not been reported outside Australia, this similarity suggests the population sequenced represents the progeny of either an indigenous virus that spread from a native legume to subterranean clover after its introduction or a recent seed-borne incursion from elsewhere. The ORF1 was the most variable, and the phylogenetic tree constructed with ORF1s showed the isolates grouped according to their symptom severity in subterranean clover, indicating the probability that ORF1-encoded P1 protein is a symptom determinant. A satellite RNA was associated with all SCMoV genomes obtained by HTS but none derived by SS.

Forty-year-old beet ringspot virus isolate: tests for potato true seed transmission, genome sequencing, recombination analysis and phylogenetic placement - Roger A. C. Jones; Aimee R. Fowkes; Sam McGreig; Adrian Fox; Ian P. Adams (Journal of Plant Pathology, 2022)
Summary Beet ringspot virus (BRSV) isolate IF came from a 1980 bait test on a Scottish soil sample. Between 1982 and 1984, it was used to study possible BRSV seed transmission in potato ( Solanum tuberosum ). To encourage flowering, potato scions were graft-inoculated onto tomato plants and these grafted plants were inoculated with IF. Flowers on BRSV-infected potato shoots were self-pollinated and their seeds collected. BRSV was found readily in pollen from these potato flowers, but never detected in any seedlings that grew from their seeds. Thus, although BRSV was present in pollen, no evidence of potato true seed transmission was obtained. In 1985, IF was preserved by freeze-drying and kept thereafter in a historical virus isolate collection. In 2020, it was subjected to high throughput sequencing and a complete genomic sequence was obtained. No recombination was detected in the IF sequence but its RNA1 and RNA2 were major parents of three, and a minor parent of one, recombinant BRSV isolates, respectively. Phylogenetic analysis of the P1 and P2 components of the coat protein gene encoded on its RNA2 placed the isolate IF sequence within the BRSV lineage. However, too few other BRSV sequences from different countries were present to provide information on its geographical associations.

Improving sightings-derived residency estimation for whale shark aggregations: A novel metric applied to a global data set - Gonzalo Araujo; Ariana Agustines; Steffen S. Bach; Jesse E. M. Cochran; Emilio de la Parra-Galván; Rafael de la Parra-Venegas; Stella Diamant; Alistair Dove; Steve Fox; Rachel T. Graham; Sofia M. Green; Jonathan R. Green; et al. (Frontiers in Marine Science, 2022)
The world’s largest extant fish, the whale shark Rhincodon typus , is one of the most-studied species of sharks globally. The discovery of predictable aggregation sites where these animals gather seasonally or are sighted year-round – most of which are coastal and juvenile-dominated – has allowed for a rapid expansion of research on this species. The most common method for studying whale sharks at these sites is photographic identification (photo-ID). This technique allows for long-term individual-based data to be collected which can, in turn, be used to evaluate population structure, build population models, identify long-distance movements, and assess philopatry and other population dynamics. Lagged identification rate (LIR) models have fewer underlying assumptions than more traditional capture mark recapture approaches, making them more broadly applicable to marine taxa, especially far-ranging megafauna species like whale sharks. However, the increased flexibility comes at a cost. Parameter estimations based on LIR can be difficult to interpret and may not be comparable between areas with different sampling regimes. Using a unique data-set from the Philippines with ~8 years of nearly continuous survey effort, we were able to derive a metric for converting LIR residency estimates into more intuitive days-per-year units. We applied this metric to 25 different sites allowing for the first quantitatively-meaningful comparison of sightings-derived residence among the world’s whale shark aggregations. We validated these results against the only three published acoustic residence metrics (falling within the ranges established by these earlier works in all cases). The results were then used to understand residency behaviours exhibited by the sharks at each site. The adjusted residency metric is an improvement to LIR-based population modelling, already one of the most widely used tools for describing whale shark aggregations. The standardised methods presented here can serve as a valuable tool for assessing residency patterns of whale sharks, which is crucial for tailored conservation action, and can cautiously be tested in other taxa.

Influence of Rising Water Temperature on the Temperate Seagrass Species Eelgrass (Zostera marina L.) in the Northeast USA - Holly K. Plaisted; Erin C. Shields; Alyssa B. Novak; Christopher P. Peck; Forest Schenck; Jillian Carr; Paul A. Duffy; N. Tay Evans; Sophia E. Fox; Stephen M. Heck; Robbie Hudson; Trevor Mattera; et al. (Frontiers in Marine Science, 2022)
Sea surface temperature (SST) has increased worldwide since the beginning of the 20th century, a trend which is expected to continue. Changes in SST can have significant impacts on marine biota, including population-level shifts and alterations in community structure and diversity, and changes in the timing of ecosystem events. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems, where they provide many ecosystem services. Eelgrass, Zostera marina L., is the dominant seagrass species in the Northeast United States of America (USA). Multiple factors have been cited for losses in this region, including light reduction, eutrophication, and physical disturbance. Warming has the potential to exacerbate seagrass loss. Here, we investigate regional changes in eelgrass presence and abundance in relation to local water temperature using monitoring data from eight sites in the Northeastern USA (New Hampshire to Maryland) where a consistent monitoring protocol, SeagrassNet, has been applied. We use a hurdle model consisting of a generalized additive mixed model (GAMM) with binomial and beta response distributions for modeling eelgrass presence and abundance, respectively, in relation to the local summer average water temperature. We show that summer water temperature one year prior to monitoring is a significant predictor of eelgrass presence, but not abundance, on a regional scale. Above average summer temperatures correspond to a decrease in probability of eelgrass presence (and increased probability of eelgrass absence) the following year. Cooler than average temperatures in the preceding year, down to approximately 0.5°C below the site average, are associated with the highest predicted probability of eelgrass presence. Our findings suggest vulnerability in eelgrass meadows of the Northeast USA and emphasize the value of unified approaches to seagrass monitoring, conservation and management at the seascape scale.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

High throughput sequencing of a 42 year-old isolate of hogweed virus 4 (HV4) reveals that is a member of the genus Chordovirus - Adrian Fox; Aimee Fowkes; Ines Vazquez-Iglesias; Christine Conyers; Ben Barrett; Sam McGreig; Ian P. Adams (Journal of Plant Pathology, 2022)

Nowcasting Earthquakes by Visualizing the Earthquake Cycle with Machine Learning: A Comparison of Two Methods - John B. Rundle; Andrea Donnellan; Geoffrey Fox; James P. Crutchfield (Surveys in Geophysics, 2022)

Cancer microenvironment and genomics: evolution in process - Stanley P. Leong; Isaac P. Witz; Orit Sagi-Assif; Sivan Izraely; Jonathan Sleeman; Brian Piening; Bernard A. Fox; Carlo B. Bifulco; Rachel Martini; Lisa Newman; Melissa Davis; Lauren M. Sanders; et al. (Clinical & Experimental Metastasis, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Azole‐resistant Aspergillus fumigatus is highly prevalent in the environment of Vietnam, with marked variability by land use type - Tra‐My N. Duong; Thanh‐Van Le; Khanh‐Linh H. Tran; Phuong‐Tuyen Nguyen; Bich‐Phuong T. Nguyen; Thu‐Anh Nguyen; Huong‐Lan P. Nguyen; Bich‐Ngoc T. Nguyen; Matthew C. Fisher; Johanna Rhodes; Guy Marks; Greg J. Fox; et al. (Environmental Microbiology, 2021)
Summary Azole‐resistant environmental Aspergillus fumigatus presents a threat to public health but the extent of this threat in Southeast Asia is poorly described. We conducted environmental surveillance in the Mekong Delta region of Vietnam, collecting air and ground samples across key land‐use types, and determined antifungal susceptibilities of Aspergillus section Fumigati (ASF) isolates and azole concentrations in soils. Of 119 ASF isolates, 55% were resistant (or non‐wild type) to itraconazole, 65% to posaconazole and 50% to voriconazole. Azole resistance was more frequent in A. fumigatus sensu stricto isolates (95%) than other ASF species (32%). Resistant isolates and agricultural azole residues were overrepresented in samples from cultivated land. cyp51A gene sequence analysis showed 38/56 resistant A. fumigatus sensu stricto isolates carried known resistance mutations, with TR 34 /L98H most frequent (34/38).

Annual survival estimates of Taiga Anser fabalis and Tundra Bean Geese A. serrirostris wintering in The Netherlands, 1967–1987 - Anthony D. Fox; Morten Frederiksen; Thomas Heinicke; Kevin K. Clausen; Henk P. van der Jeugd (Journal of Ornithology, 2021)

Proprioceptive recalibration following implicit visuomotor adaptation is preserved in Parkinson’s disease - Erin K. Cressman; Danielle Salomonczyk; Alina Constantin; Janis Miyasaki; Elena Moro; Robert Chen; Antonio Strafella; Susan Fox; Anthony E. Lang; Howard Poizner; Denise Y. P. Henriques (Experimental Brain Research, 2021)

Construction of an intraplate island volcano: The volcanic history of Heard Island - Jodi M. Fox; Jocelyn McPhie; Rebecca J. Carey; Fred Jourdan; Daniel P. Miggins (Bulletin of Volcanology, 2021)

Refining Fisheries Advice With Stock-Specific Ecosystem Information - Jacob W. Bentley; Mathieu G. Lundy; Daniel Howell; Steven E. Beggs; Alida Bundy; Francisco de Castro; Clive J. Fox; Johanna J. Heymans; Christopher P. Lynam; Debbi Pedreschi; Pia Schuchert; Natalia Serpetti; et al. (Frontiers in Marine Science, 2021)
Although frequently suggested as a goal for ecosystem-based fisheries management, incorporating ecosystem information into fisheries stock assessments has proven challenging. The uncertainty of input data, coupled with the structural uncertainty of complex multi-species models, currently makes the use of absolute values from such models contentious for short-term single-species fisheries management advice. Here, we propose a different approach where the standard assessment methodologies can be enhanced using ecosystem model derived information. Using a case study of the Irish Sea, we illustrate how stock-specific ecosystem indicators can be used to set an ecosystem-based fishing mortality reference point (F ECO ) within the “Pretty Good Yield” ranges for fishing mortality which form the present precautionary approach adopted in Europe by the International Council for the Exploration of the Sea (ICES). We propose that this new target, F ECO , can be used to scale fishing mortality down when the ecosystem conditions for the stock are poor and up when conditions are good. This approach provides a streamlined quantitative way of incorporating ecosystem information into catch advice and provides an opportunity to operationalize ecosystem models and empirical indicators, while retaining the integrity of current assessment models and the F MSY -based advice process.

Workflow for the Generation of Expert-Derived Training and Validation Data: A View to Global Scale Habitat Mapping - Chris M. Roelfsema; Mitchell Lyons; Nicholas Murray; Eva M. Kovacs; Emma Kennedy; Kathryn Markey; Rodney Borrego-Acevedo; Alexandra Ordoñez Alvarez; Chantel Say; Paul Tudman; Meredith Roe; Jeremy Wolff; et al. (Frontiers in Marine Science, 2021)
Our ability to completely and repeatedly map natural environments at a global scale have increased significantly over the past decade. These advances are from delivery of a range of on-line global satellite image archives and global-scale processing capabilities, along with improved spatial and temporal resolution satellite imagery. The ability to accurately train and validate these global scale-mapping programs from what we will call “reference data sets” is challenging due to a lack of coordinated financial and personnel resourcing, and standardized methods to collate reference datasets at global spatial extents. Here, we present an expert-driven approach for generating training and validation data on a global scale, with the view to mapping the world’s coral reefs. Global reefs were first stratified into approximate biogeographic regions, then per region reference data sets were compiled that include existing point data or maps at various levels of accuracy. These reference data sets were compiled from new field surveys, literature review of published surveys, and from individually sourced contributions from the coral reef monitoring and management agencies. Reference data were overlaid on high spatial resolution satellite image mosaics (3.7 m × 3.7 m pixels; Planet Dove) for each region. Additionally, thirty to forty satellite image tiles; 20 km × 20 km) were selected for which reference data and/or expert knowledge was available and which covered a representative range of habitats. The satellite image tiles were segmented into interpretable groups of pixels which were manually labeled with a mapping category via expert interpretation. The labeled segments were used to generate points to train the mapping models, and to validate or assess accuracy. The workflow for desktop reference data creation that we present expands and up-scales traditional approaches of expert-driven interpretation for both manual habitat mapping and map training/validation. We apply the reference data creation methods in the context of global coral reef mapping, though our approach is broadly applicable to any environment. Transparent processes for training and validation are critical for usability as big data provide more opportunities for managers and scientists to use global mapping products for science and conservation of vulnerable and rapidly changing ecosystems.

Direct Stacked Investment Is a Flexible Reproductive Strategy for Female Colobus vellerosus - J. V. Vayro; T. E. Ziegler; L. M. Fedigan; A. Crotty; S. A. Fox; P. Sicotte (International Journal of Primatology, 2021)

A juvenile Tristan albatross (Diomedea dabbenena) on land at the Crozet Islands - Alexander L. Bond; Christopher Taylor; David Kinchin-Smith; Derren Fox; Emma Witcutt; Peter G. Ryan; Simon P. Loader; Henri Weimerskirch (Polar Biology, 2021)
Albatrosses and other seabirds are generally highly philopatric, returning to natal colonies when they achieve breeding age. This is not universal, however, and cases of extraordinary vagrancy are rare. The Tristan Albatross ( Diomedea dabbenena ) breeds on Gough Island in the South Atlantic Ocean, with a small population on Inaccessible Island, Tristan da Cunha, ca 380 km away. In 2015, we observed an adult male albatross in Gonydale, Gough Island, which had been ringed on Ile de la Possession, Crozet Islands in 2009 when it was assumed to be an immature Wandering Albatross ( D. exulans ). We sequenced 1109 bp of the cytochrome b mitochondrial gene from this bird, and confirmed it to be a Tristan Albatross, meaning its presence on Crozet 6 years previous, and nearly 5000 km away, was a case of prospecting behaviour in a heterospecific colony. Given the challenges in identifying immature Diomedea albatrosses, such dispersal events may be more common than thought previously.

Author Correction: Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)

Resolving and Parameterising the Ocean Mesoscale in Earth System Models - Helene T. Hewitt; Malcolm Roberts; Pierre Mathiot; Arne Biastoch; Ed Blockley; Eric P. Chassignet; Baylor Fox-Kemper; Pat Hyder; David P. Marshall; Ekaterina Popova; Anne-Marie Treguier; Laure Zanna; et al. (Current Climate Change Reports, 2020)
Purpose of Review Assessment of the impact of ocean resolution in Earth System models on the mean state, variability, and future projections and discussion of prospects for improved parameterisations to represent the ocean mesoscale. Recent Findings The majority of centres participating in CMIP6 employ ocean components with resolutions of about 1 degree in their full Earth System models (eddy-parameterising models). In contrast, there are also models submitted to CMIP6 (both DECK and HighResMIP) that employ ocean components of approximately 1/4 degree and 1/10 degree (eddy-present and eddy-rich models). Evidence to date suggests that whether the ocean mesoscale is explicitly represented or parameterised affects not only the mean state of the ocean but also the climate variability and the future climate response, particularly in terms of the Atlantic meridional overturning circulation (AMOC) and the Southern Ocean. Recent developments in scale-aware parameterisations of the mesoscale are being developed and will be included in future Earth System models. Summary Although the choice of ocean resolution in Earth System models will always be limited by computational considerations, for the foreseeable future, this choice is likely to affect projections of climate variability and change as well as other aspects of the Earth System. Future Earth System models will be able to choose increased ocean resolution and/or improved parameterisation of processes to capture physical processes with greater fidelity.

Evidence of diverse movement strategies and habitat use by white sharks, Carcharodon carcharias, off southern Australia - Russell Bradford; T. A. Patterson; P. J. Rogers; R. McAuley; S. Mountford; C. Huveneers; R. Robbins; A. Fox; B. D. Bruce (Marine Biology, 2020)
Large endothermic pelagic sharks are highly migratory and use habitats spanning a broad range of coastal, neritic and oceanic areas. This study aimed to resolve the current lack of information on the movements and habitat use of white sharks, Carcharodon carcharias , between shelf, slope and oceanic areas located off southwestern Australia. Movement behaviours, spatial distribution patterns and vertical habitat use of juvenile, sub-adult and adult white sharks ranging in size from 1.9 to 5.7 m total length were examined using 43 satellite tags deployed over 15 years. Pop-up satellite archival tags and satellite-linked radio tags collected 3663 days and > 109,900 km of tracking data over periods of up to 381 days. We demonstrated sex-based differences in movement and distribution patterns of male (21) and female (19) white sharks. Female dispersal was broader and extended further offshore than males, which largely remained in neritic and gulf habitats. Female white sharks experienced a narrower range of water temperatures ( F = 9.0–19.0 °C; M = 10.4–24.8 °C). Despite these subtle differences, both sexes showed an affinity to the Neptune Island Group and the shelf slope canyons of the eastern Great Australian Bight, which are productive and oceanographically complex regions that support known prey of white sharks. This study highlighted that the southern-western Australian population of white sharks use off-shelf habitat to a greater extent than previously identified. Findings have potential implications for: ecological risk assessments of fisheries that operate in these offshore habitats and for monitoring and managing marine protected areas.

Sediment deposition in the central Hauraki Gulf, New Zealand - Florian Boxberg; Brice Blossier; Willem P. de Lange; Bethany Fox; Dierk Hebbeln (Geo-Marine Letters, 2020)

Genomic sequence and host range studies reveal considerable variation within the species Arracacha virus B - Roger A. C. Jones; Adrian Fox; Neil Boonham; Ian P. Adams (Archives of Virology, 2019)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

Climate change in context: putting people first in the Arctic - Henry P. Huntington; Mark Carey; Charlene Apok; Bruce C. Forbes; Shari Fox; Lene K. Holm; Aitalina Ivanova; Jacob Jaypoody; George Noongwook; Florian Stammler (Regional Environmental Change, 2019)

The U.S. Climate Resilience Toolkit: evidence of progress - Edward P. Gardiner; David D. Herring; James F. Fox (Climatic Change, 2019)

Challenges and Prospects in Ocean Circulation Models - Baylor Fox-Kemper; Alistair Adcroft; Claus W. Böning; Eric P. Chassignet; Enrique Curchitser; Gokhan Danabasoglu; Carsten Eden; Matthew H. England; Rüdiger Gerdes; Richard J. Greatbatch; Stephen M. Griffies; Robert W. Hallberg; et al. (Frontiers in Marine Science, 2019)

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

Assessing nitrogen and phosphorus removal potential of five plant species in floating treatment wetlands receiving simulated nursery runoff - Jonathan T. Spangler; David J. Sample; Laurie J. Fox; Joseph P. Albano; Sarah A. White (Environmental Science and Pollution Research, 2019)

The impact of high throughput sequencing on plant health diagnostics - Ian P. Adams; Adrian Fox; Neil Boonham; Sébastien Massart; Kris De Jonghe (European Journal of Plant Pathology, 2018)

Novel frontiers in detecting cancer metastasis - Stanley P. Leong; Carmen Ballesteros-Merino; Shawn M. Jensen; Sebastian Marwitz; Carlo Bifulco; Bernard A. Fox; Mojca Skoberne (Clinical & Experimental Metastasis, 2018)

Revisiting “Success” and “Failure” of Marine Protected Areas: A Conservation Scientist Perspective - Sylvaine Giakoumi; Jennifer McGowan; Morena Mills; Maria Beger; Rodrigo H. Bustamante; Anthony Charles; Patrick Christie; Matthew Fox; Pablo Garcia-Borboroglu; Stefan Gelcich; Paolo Guidetti; Peter Mackelworth; et al. (Frontiers in Marine Science, 2018)

Corrigendum: Composition of Dissolved Organic Matter in Pore Waters of Anoxic Marine Sediments Analyzed by 1H Nuclear Magnetic Resonance Spectroscopy - Christina A. Fox; Hussain A. Abdulla; David J. Burdige; James P. Lewicki; Tomoko Komada (Frontiers in Marine Science, 2018)

Composition of Dissolved Organic Matter in Pore Waters of Anoxic Marine Sediments Analyzed by 1H Nuclear Magnetic Resonance Spectroscopy - Christina A. Fox; Hussain A. Abdulla; David J. Burdige; James P. Lewicki; Tomoko Komada (Frontiers in Marine Science, 2018)

The Application of Pulsed Electromagnetic Fields (PEMFs) for Bone Fracture Repair: Past and Perspective Findings - C. Daish; R. Blanchard; K. Fox; P. Pivonka; E. Pirogova (Annals of Biomedical Engineering, 2018)

Trace element and strontium isotopic analysis of Gulf Sturgeon fin rays to assess habitat use - P. J. Allen; R. J. DeVries; D. A. Fox; R. I. Gabitov; W. G. Anderson (Environmental Biology of Fishes, 2018)

Staying in place during times of change in Arctic Alaska: the implications of attachment, alternatives, and buffering - Henry P. Huntington; Philip A. Loring; Glenna Gannon; Shari Fox Gearheard; S. Craig Gerlach; Lawrence C. Hamilton (Regional Environmental Change, 2018)

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

Adapting astronomical source detection software to help detect animals in thermal images obtained by unmanned aerial systems - S. N. Longmore; R. P. Collins; S. Pfeifer; S. E. Fox; M. Mulero-Pázmány; F. Bezombes; A. Goodwin; M. De Juan Ovelar; J. H. Knapen; S. A. Wich (International Journal of Remote Sensing, 2017)

Strong fisheries management and governance positively impact ecosystem status - Alida Bundy; Ratana Chuenpagdee; Jennifer L Boldt; Maria de Fatima Borges; Mohamed Lamine Camara; Marta Coll; Ibrahima Diallo; Clive Fox; Elizabeth A Fulton; Ayse Gazihan; Astrid Jarre; Didier Jouffre; et al. (Fish and Fisheries, 2017)
Fisheries have had major negative impacts on marine ecosystems, and effective fisheries management and governance are needed to achieve sustainable fisheries, biodiversity conservation goals and thus good ecosystem status. To date, the IndiSeas programme (Indicators for the Seas) has focussed on assessing the ecological impacts of fishing at the ecosystem scale using ecological indicators. Here, we explore fisheries ‘Management Effectiveness’ and ‘Governance Quality’ and relate this to ecosystem health and status. We developed a dedicated expert survey, focused at the ecosystem level, with a series of questions addressing aspects of management and governance, from an ecosystem‐based perspective, using objective and evidence‐based criteria. The survey was completed by ecosystem experts (managers and scientists) and results analysed using ranking and multivariate methods. Results were further examined for selected ecosystems, using expert knowledge, to explore the overall findings in greater depth. Higher scores for ‘Management Effectiveness’ and ‘Governance Quality’ were significantly and positively related to ecosystems with better ecological status. Key factors that point to success in delivering fisheries and conservation objectives were as follows: the use of reference points for management, frequent review of stock assessments, whether Illegal, Unreported and Unregulated ( IUU ) catches were being accounted for and addressed, and the inclusion of stakeholders. Additionally, we found that the implementation of a long‐term management plan, including economic and social dimensions of fisheries in exploited ecosystems, was a key factor in successful, sustainable fisheries management. Our results support the thesis that good ecosystem‐based management and governance, sustainable fisheries and healthy ecosystems go together.

Balancing ecosystem function, services and disservices resulting from expanding goose populations - Ralph Buij; Theodorus C. P. Melman; Maarten J. J. E. Loonen; Anthony D. Fox (Ambio, 2017)

Connectivity between the central nucleus of the amygdala and the bed nucleus of the stria terminalis in the non-human primate: neuronal tract tracing and developmental neuroimaging studies - Jonathan A. Oler; Do P. M. Tromp; Andrew S. Fox; Rothem Kovner; Richard J. Davidson; Andrew L. Alexander; Daniel R. McFarlin; Rasmus M. Birn; Benjamin E. Berg; Danielle M. deCampo; Ned H. Kalin; Julie L. Fudge (Brain Structure and Function, 2017)

Natural hazards in Australia: extreme bushfire - Jason J. Sharples; Geoffrey J. Cary; Paul Fox-Hughes; Scott Mooney; Jason P. Evans; Michael-Shawn Fletcher; Mike Fromm; Pauline F. Grierson; Rick McRae; Patrick Baker (Climatic Change, 2016)

Non-normal distribution of the top-of-atmosphere satellite optical measurements over calibration sites - Javier Gorroño; Agnieszka Bialek; Paul D. Green; Peter Harris; Tracy Scanlon; Nigel P. Fox; Craig Underwood (International Journal of Remote Sensing, 2016)

The Microbiota, Immunoregulation, and Mental Health: Implications for Public Health - Christopher A. Lowry; David G. Smith; Philip H. Siebler; Dominic Schmidt; Christopher E. Stamper; James E. Hassell; Paula S. Yamashita; James H. Fox; Stefan O. Reber; Lisa A. Brenner; Andrew J. Hoisington; Teodor T. Postolache; et al. (Current Environmental Health Reports, 2016)

In vitro experimental environments lacking or containing soil disparately affect competition experiments of Aspergillus flavus and co-occurring fungi in maize grains - Titilayo D.O. Falade; Sharifah H. Syed Mohdhamdan; Yasmina Sultanbawa; Mary T. Fletcher; Jagger J.W. Harvey; Mridusmita Chaliha; Glen P. Fox (Food Additives & Contaminants: Part A, 2016)

Geological development of Heard Island, Central Kerguelen Plateau - R. A. Duncan; P. G. Quilty; J. Barling; J. M. Fox (Australian Journal of Earth Sciences, 2016)

Discovery of QTL for stay-green and heat-stress in barley (Hordeum vulgare) grown under simulated abiotic stress conditions - Peter W. Gous; Lee Hickey; Jack T. Christopher; Jerome Franckowiak; Glen P. Fox (Euphytica, 2016)

Chemical characterization and in vitro toxicity of diesel exhaust particulate matter generated under varying conditions - Julie Richman Fox; David P. Cox; Bertram E. Drury; Timothy R. Gould; Terrance J. Kavanagh; Michael H. Paulsen; Lianne Sheppard; Christopher D. Simpson; James A. Stewart; Timothy V. Larson; Joel D. Kaufman (Air Quality, Atmosphere & Health, 2015)

Abundance of common species, not species richness, drives delivery of a real‐world ecosystem service - Rachael Winfree; Jeremy W. Fox; Neal M. Williams; James R. Reilly; Daniel P. Cariveau (Ecology Letters, 2015)
Biodiversity‐ecosystem functioning experiments have established that species richness and composition are both important determinants of ecosystem function in an experimental context. Determining whether this result holds for real‐world ecosystem services has remained elusive, however, largely due to the lack of analytical methods appropriate for large‐scale, associational data. Here, we use a novel analytical approach, the Price equation, to partition the contribution to ecosystem services made by species richness, composition and abundance in four large‐scale data sets on crop pollination by native bees. We found that abundance fluctuations of dominant species drove ecosystem service delivery, whereas richness changes were relatively unimportant because they primarily involved rare species that contributed little to function. Thus, the mechanism behind our results was the skewed species‐abundance distribution. Our finding that a few common species, not species richness, drive ecosystem service delivery could have broad generality given the ubiquity of skewed species‐abundance distributions in nature.

Legacy Effects of Different Land-Use Histories Interact with Current Grazing Patterns to Determine Grazing Lawn Soil Properties - Hugo Valls Fox; Olivier Bonnet; Joris P. G. M. Cromsigt; Hervé Fritz; Adrian M. Shrader (Ecosystems, 2015)

Formalizing the semantics of sea ice - Ruth E. Duerr; Jamie P. McCusker; Mark A. Parsons; SiriJodha Singh Khalsa; Peter L. Pulsifer; Cassidy Thompson; Rui Yan; Deborah L. McGuinness; Peter Fox (Earth Science Informatics, 2015)

The role of the right temporoparietal junction in attention and social interaction as revealed by ALE meta-analysis - S. C. Krall; C. Rottschy; E. Oberwelland; D. Bzdok; P. T. Fox; S. B. Eickhoff; G. R. Fink; K. Konrad (Brain Structure and Function, 2015)

Multiplication of microbes below 0.690 water activity: implications for terrestrial and extraterrestrial life - Andrew Stevenson; Jürgen Burkhardt; Charles S. Cockell; Jonathan A. Cray; Jan Dijksterhuis; Mark Fox‐Powell; Terence P. Kee; Gerhard Kminek; Terry J. McGenity; Kenneth N. Timmis; David J. Timson; Mary A. Voytek; et al. (Environmental Microbiology, 2015)
Summary Since a key requirement of known life forms is available water (water activity; a w ), recent searches for signatures of past life in terrestrial and extraterrestrial environments have targeted places known to have contained significant quantities of biologically available water. However, early life on E arth inhabited high‐salt environments, suggesting an ability to withstand low water‐activity. The lower limit of water activity that enables cell division appears to be ∼ 0.605 which, until now, was only known to be exhibited by a single eukaryote, the sugar‐tolerant, fungal xerophile X eromyces bisporus . The first forms of life on E arth were, though, prokaryotic. Recent evidence now indicates that some halophilic A rchaea and B acteria have water‐activity limits more or less equal to those of X . bisporus . We discuss water activity in relation to the limits of E arth's present‐day biosphere; the possibility of microbial multiplication by utilizing water from thin, aqueous films or non‐liquid sources; whether prokaryotes were the first organisms able to multiply close to the 0.605‐a w limit; and whether extraterrestrial aqueous milieux of ≥ 0.605 a w can resemble fertile microbial habitats found on Earth.

Genome sequence of vanilla distortion mosaic virus infecting Coriandrum sativum - I. P. Adams; S. Rai; M. Deka; V. Harju; T. Hodges; G. Hayward; A. Skelton; A. Fox; N. Boonham (Archives of Virology, 2014)

Large multiethnic Candidate Gene Study for C-reactive protein levels: identification of a novel association at CD36 in African Americans - Jaclyn Ellis; Ethan M. Lange; Jin Li; Josee Dupuis; Jens Baumert; Jeremy D. Walston; Brendan J. Keating; Peter Durda; Ervin R. Fox; Cameron D. Palmer; Yan A. Meng; Taylor Young; et al. (Human Genetics, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Mutant strains of Pichia pastoris with enhanced secretion of recombinant proteins - Sasha Larsen; Jun Weaver; Katherine de Sa Campos; Rhobe Bulahan; Jackson Nguyen; Heather Grove; Amy Huang; Lauren Low; Namphuong Tran; Seth Gomez; Jennifer Yau; Thomas Ilustrisimo; et al. (Biotechnology Letters, 2013)

Differentiated parietal connectivity of frontal regions for “what” and “where” memory - C. Rottschy; S. Caspers; C. Roski; K. Reetz; I. Dogan; J. B. Schulz; K. Zilles; A. R. Laird; P. T. Fox; S. B. Eickhoff (Brain Structure and Function, 2013)

QTLs for water absorption and flour yield identified in the doubled haploid wheat population Lang/QT8766 - G. P. Fox; A. Martin; A. M. Kelly; M. W. Sutherland; D. Martin; P. M. Banks; J. Sheppard (Euphytica, 2013)

Respiratory C fluxes and root exudation differ in two full-sib clones of Pinus taeda (L.) under contrasting fertilizer regimes in a greenhouse - Jeremy P. Stovall; John R. Seiler; Thomas R. Fox (Plant and Soil, 2013)

Correlation between NIRS generated and chemically measured feed quality data in barley (Hordeum vulgare), and potential use in QTL analysis identification - Peter W. Gous; Anke Martin; Wendy Lawson; Alison Kelly; Glen P. Fox; Mark W. Sutherland (Euphytica, 2012)

Developing standardized methods for breeding preharvest sprouting resistant wheat, challenges and successes in Canadian wheat - R. M. DePauw; R. E. Knox; A. K. Singh; S. L. Fox; D. G. Humphreys; P. Hucl (Euphytica, 2012)

cry1 and GPA1 signaling genetically interact in hook opening and anthocyanin synthesis in Arabidopsis - Ana R. Fox; Gabriela C. Soto; Alan M. Jones; Jorge J. Casal; Jorge P. Muschietti; María A. Mazzella (Plant Molecular Biology, 2012)

Short-term changes in biomass partitioning of two full-sib clones of Pinus taeda L. under differing fertilizer regimes over 4 months - Jeremy P. Stovall; Thomas R. Fox; John R. Seiler (Trees, 2012)

Demographic heterogeneity impacts density-dependent population dynamics - Joseph P. Stover; Bruce E. Kendall; Gordon A. Fox (Theoretical Ecology, 2012)

QTL associated with barley (Hordeum vulgare) feed quality traits measured through in situ digestion - Peter W. Gous; Anke Martin; Wendy Lawson; Alison Kelly; Glen P. Fox; Mark W. Sutherland (Euphytica, 2012)

Obituary: David H. Reed (24 March 1963–24 October 2011) - Richard Frankham; George A. Gale; Charles W. Fox; Edwin H. Bryant; Brice P. Noonan; Robert B. Page; Kathy Traylor-Holzer; Torsten N. Kristensen (Conservation Genetics, 2012)

Plasma gelsolin accumulates in macrophage nodules in brains of simian immunodeficiency virus infected rhesus macaques - T. Jagadish; G. Pottiez; H. S. Fox; P. Ciborowski (Journal of NeuroVirology, 2012)

Aging impairs the mobilization and homing of bone marrow-derived angiogenic cells to burn wounds - Xianjie Zhang; Kakali Sarkar; Sergio Rey; Raul Sebastian; Efstathia Andrikopoulou; Guy P. Marti; Karen Fox-Talbot; Gregg L. Semenza; John W. Harmon (Journal of Molecular Medicine, 2011)

A comparison of two microbial detection methods used in aseptic processing of musculoskeletal allograft tissues - Jeremy A. Dennis; Octavio V. Martinez; David C. Landy; Theodore I. Malinin; Paul R. Morris; William P. Fox; Billy E. Buck; H. Thomas Temple (Cell and Tissue Banking, 2011)

Distributions, life‐history specialization, and phylogeny of the rain forest vertebrates in the Australian Wet Tropics - S. E. Williams; J. VanDerWal; J. Isaac; L. P. Shoo; C. Storlie; S. Fox; E. E. Bolitho; C. Moritz; C. J. Hoskin; Y. M. Williams (Ecology, 2010)
The purpose of this data set was to compile distributional, general life‐history characteristics and phylogenies for Australian tropical rain forest vertebrates to inform a wide range of comparative studies on the determinants of biodiversity patterns and to assess the impacts of global climate change. We provide three distinct data sets: (1) a table of species‐specific distributional and life‐history traits for 242 vertebrate species found in the rain forests of the Australian Wet Tropics; (2) species distribution maps (GIS raster files) for 202 of the species displaying both the realized and potential distributions; and (3) phylogenies for these species. These species represent 93 birds, 31 amphibians, 31 mammals (including one monotreme), and 47 reptiles. Where information exists, the distributional and life‐history data compiled here present information on: indices of environmental specialization (ENFA), habitat specialization, average body mass and size, sexual dimorphism, reproductive characteristics such as age at first reproduction, clutch/litter size, number of reproductive bouts per year and breeding seasonality, longevity, time of day when most active, and dispersal ability; distributional characteristics such as range size (potential and realized for both total and core ranges) and observed ranges in temperature, precipitation, and elevation; and niche attributes such as environmental marginality and specialization. The distribution maps provided represent a combination of presence‐only ecological niche modeling (using MaxEnt) to estimate the potential distribution of a species followed by biogeographic clipping by expert opinion based on extensive field data and a subregional classification relevant to the topography and biogeographic history of the region to produce best‐possible estimates of the realized distribution. Our assemblage contains many species with a shared evolutionary history, and thus many analyses of these data will need to account for phylogeny. Although a comprehensive phylogeny with branch length information does not exist for this diverse group of species, we present a best‐estimate composite phylogeny constructed primarily from recently published molecular phylogenies of included groups. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Positive Allosteric Interaction of Structurally Diverse T-Type Calcium Channel Antagonists - Victor N. Uebele; Cindy E. Nuss; Steven V. Fox; Susan L. Garson; Razvan Cristescu; Scott M. Doran; Richard L. Kraus; Vincent P. Santarelli; Yuxing Li; James C. Barrow; Zhi-Qiang Yang; Kelly-Ann S. Schlegel; et al. (Cell Biochemistry and Biophysics, 2009)

Grid in earth sciences - M. Petitdidier; R. Cossu; P. Mazzetti; P. Fox; H. Schwichtenberg; W. Som de Cerff (Earth Science Informatics, 2009)

Host specificity of Ischnodemus variegatus, an herbivore of West Indian marsh grass (Hymenachne amplexicaulis) - Rodrigo Diaz; William A. Overholt; James P. Cuda; Paul D. Pratt; Alison Fox (BioControl, 2009)

Host specificity of Ischnodemus variegatus, an herbivore of West Indian marsh grass (Hymenachne amplexicaulis) - Rodrigo Diaz; William A. Overholt; James P. Cuda; Paul D. Pratt; Alison Fox (BioControl, 2009)

Nitrogen Phytoremediation by Water Hyacinth (Eichhornia crassipes (Mart.) Solms) - L. J. Fox; P. C. Struik; B. L. Appleton; J. H. Rule (Water, Air, & Soil Pollution, 2008)

Assessing for genetic and environmental effects on ruminant feed quality in barley (Hordeum vulgare) - Glen P. Fox; Jan Bowman; Alison Kelly; Andy Inkerman; David Poulsen; Robert Henry (Euphytica, 2008)

Is fecundity in plaice ( Pleuronectes platessa L.) down‐regulated in response to reduced food intake during autumn? - J. Kennedy; P. R. Witthames; R. D. M. Nash; C. J. Fox (Journal of Fish Biology, 2008)
The effect of controlling food intake during the autumn, which is the time of late vitellogenesis, on fecundity, atresia and follicle and ovary growth was examined for plaice Pleuronectes platessa . Eighteen fish were kept in individual pens and either fed on a high or low ration diet. Fish which increased in whole body condition exhibited an increase in carcass condition which means that when food intake is sufficient to maintain whole body condition some resources are used as storage. Follicle growth rate was positively correlated with change in Fulton’s condition and total atresia was negatively correlated with change in Fulton’s condition. Thus, the rate of vitellogenesis was dependent on the availability of an exogenous food source. Fecundity at the end of the experiment was positively correlated with mass and total length. Food intake had no effect on relative fecundity; however, fish which had a lower food intake lost mass and had a greater intensity of atresia, lowering their absolute fecundity. One fish in a very low condition at the start of the experiment skipped spawning and one fish exhibited a decrease in average follicle diameter during the experiment which is hypothesized to be a prelude to mass atresia.

Dissecting the evolutionary impacts of plant invasions: bugs and beetles as native guides - SCOTT P. CARROLL; CHARLES W. FOX (Global Change Biology, 2007)
The introduction of plants into new biogeographical realms is a main repercussion of human trade. The responses of native insects to alien plants may provide insight into how invaders influence ecological processes in their new communities. We illustrate this point with results from our field and lab studies of seed‐feeding insects on alien plants. Soapberry bugs ( Jadera , Leptocoris ) have colonized several species of weedy invasive plants (sapindaceous trees and vines) in the United States and Australia. After initial reduction in physiological performance, they evolved behavioral, morphological, physiological and life history adaptations permitting more efficient exploitation of those hosts. Those changes occurred quickly, in fewer than 100 generations (ca. 30–50 years). The underlying genetic changes are surprisingly complex, and also involve loss of function on native hosts. Contrasting with this is the bruchine beetle ( Stator limbatus ) on seeds of leguminous trees. Large numbers of S. limbatus oviposit on an alien tree in Arizona, but few offspring survive. The main influence on larval survival is a maternal effect determined by the host the mother experiences as her eggs mature. Adaptive plasticity in egg size and composition may ultimately permit successful exploitation of novel resources. Together, these studies show that both complex genetic and developmental factors influence the integration of ecological and evolutionary processes in environments altered by anthropogenically initiated plant invasions. Tractable insect study systems may be valuable guides to understanding biotic dynamics in a changing world.

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

The importance of individual behaviour for successful settlement of juvenile plaice ( Pleuronectes platessa L.): a modelling and field study in the eastern Irish Sea - C. J. FOX; P. MCCLOGHRIE; E. F. YOUNG; R. D. M. NASH (Fisheries Oceanography, 2006)
To study the transport of plaice ( Pleuronectes platessa L.) eggs and larvae in the eastern Irish Sea, we constructed a 3D‐baroclinic physical model and coupled it to a particle‐tracking scheme that allowed aspects of larval behaviour to be simulated. Starting positions for eggs were based upon data from a series of ichthyoplankton surveys and final positions were compared with results of settled plaice distributions from two beam trawl surveys conducted on beaches around the eastern Irish Sea. If simulated larval behaviour was limited to passive drift or horizontal swimming, the particles diffused away from the spawning areas but failed to reach nursery grounds in significant numbers (85–90% remaining offshore). In contrast, switching on circatidal vertical swimming significantly increased the numbers of larvae reaching the coast (only 23–30% remained offshore). Particles tended to accumulate in bays and estuaries and this pattern compared well with the distribution of settled plaice from the field surveys. Studies in the southern North Sea (where spawning and nursery grounds are widely separated) have also demonstrated the importance of selective tidal stream transport for successful recruitment of settling plaice to nursery grounds. Although our understanding of the ontogeny of this behaviour is still poor, the model results presented suggest that this aspect of behaviour is a key factor influencing plaice settlement success.

Indole-3-carbinol-induced death in cancer cells involves EGFR downregulation and is exacerbated in a 3D environment - E. P. Moiseeva; L. H. Fox; L. M. Howells; L. A. F. Temple; M. M. Manson (Apoptosis, 2006)

Tree Performance and Root-Zone Salt Accumulation in Three Dryland Australian Plantations - Robert D. Archibald; Richard J. Harper; John E. D. Fox; Richard P. Silberstein (Agroforestry Systems, 2006)

Fishes and salinities in the St Lucia estuarine system—a review - Alan K. Whitfield; Ricky H. Taylor; Caroline Fox; Digby P. Cyrus (Reviews in Fish Biology and Fisheries, 2006)

Rapid evolution and the convergence of ecological and evolutionary time - Nelson G. Hairston; Stephen P. Ellner; Monica A. Geber; Takehito Yoshida; Jennifer A. Fox (Ecology Letters, 2005)
Recent studies have documented rates of evolution of ecologically important phenotypes sufficiently fast that they have the potential to impact the outcome of ecological interactions while they are underway. Observations of this type go against accepted wisdom that ecological and evolutionary dynamics occur at very different time scales. While some authors have evaluated the rapidity of a measured evolutionary rate by comparing it to the overall distribution of measured evolutionary rates, we believe that ecologists are mainly interested in rapid evolution because of its potential to impinge on ecological processes. We therefore propose that rapid evolution be defined as a genetic change occurring rapidly enough to have a measurable impact on simultaneous ecological change. Using this definition we propose a framework for decomposing rates of ecological change into components driven by simultaneous evolutionary change and by change in a non‐evolutionary factor (e.g. density dependent population dynamics, abiotic environmental change). Evolution is judged to be rapid in this ecological context if its contribution to ecological change is large relative to the contribution of other factors. We provide a worked example of this approach based on a theoretical predator–prey interaction [ Abrams, P. & Matsuda, H. (1997) . Evolution , 51, 1740], and find that in this system the impact of prey evolution on predator per capita growth rate is 63% that of internal ecological dynamics. We then propose analytical methods for measuring these contributions in field situations, and apply them to two long‐term data sets for which suitable ecological and evolutionary data exist. For both data sets relatively high rates of evolutionary change have been found when measured as character change in standard deviations per generation (haldanes). For Darwin's finches evolving in response to fluctuating rainfall [ Grant, P.R. & Grant, B.R. (2002) . Science , 296, 707], we estimate that evolutionary change has been more rapid than ecological change by a factor of 2.2. For a population of freshwater copepods whose life history evolves in response to fluctuating fish predation [ Hairston, N.G. Jr & Dillon, T.A. (1990) . Evolution , 44, 1796], we find that evolutionary change has been about one quarter the rate of ecological change – less than in the finch example, but nevertheless substantial. These analyses support the view that in order to understand temporal dynamics in ecological processes it is critical to consider the extent to which the attributes of the system under investigation are simultaneously changing as a result of rapid evolution.

Prey size selection and distance estimation in foraging adult dragonflies - R. M. Olberg; A. H. Worthington; J. L. Fox; C. E. Bessette; M. P. Loosemore (Journal of Comparative Physiology A, 2005)

2. Histaminergic mechanisms in the CNS - G. B. Fox; T. A. Esbenshade; J. B. Pan; K. E. Browman; M. Zhang; M. E. Ballard; R. J. Radek; H. Miner; R. S. Bitner; K. M. Krueger; B. B. Yao; R. Faghih; et al. (Inflammation Research, 2005)

Retinal and extraocular cytomegalovirus end-organ disease in HIV-infected patients in Europe: a EuroSIDA study, 1994?2001 - I. Yust; Z. Fox; M. Burke; A. Johnson; D. Turner; A. Mocroft; C. Katlama; B. Ledergerber; P. Reiss; O. Kirk (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Long-term population trends in widespread British moths - Kelvin F. Conrad; Ian P. Woiwod; Mark Parsons; Richard Fox; Martin S. Warren (Journal of Insect Conservation, 2004)

Beta-2-microglobulin haplotypes in U.S. beef cattle and association with failure of passive transfer in newborn calves - Michael L. Clawson; Michael P. Heaton; Carol G. Chitko-McKown; James M. Fox; Timothy P. L. Smith; Warren M. Snelling; John W. Keele; William W. Laegreid (Mammalian Genome, 2004)

Cognition enhancing effects of novel H 3 receptor (H 3 R) antagonists in several animal models - G. B. Fox; J. B. Pan; A. M. Lewis; K. E. Browman; V. A. Komater; M. J. Buckley; P. Curzon; R. J. Radek; R. Faghih; T. A. Esbenshade; M. D. Cowart; M. W. Decker; et al. (Inflammation Research, 2004)

Genes encoding a fructose-1,6-bisphosphate aldolase and a fructose-1,6-bisphosphatase are present within the gene cluster for mimosine degradation in Rhizobium sp. strain TAL1145 - J. D. Awaya; P. M. Fox; D. Borthakur (Plant and Soil, 2003)

Prion gene sequence variation within diverse groups of U.S. sheep, beef cattle, and deer - Michael P. Heaton; Kreg A. Leymaster; Brad A. Freking; Deedra A. Hawk; Timothy P. L. Smith; John W. Keele; Warren M. Snelling; James M. Fox; Carol G. Chitko-McKown; William W. Laegreid (Mammalian Genome, 2003)

Comparison of molecular markers and coefficients of parentage for the analysis of genetic diversity among spring bread wheat accessions - M. I. Almanza-Pinzón; M. Khairallah; P. N. Fox; M. L. Warburton (Euphytica, 2003)

Hepatic EROD Activity is Not a Useful Biomarker of Polychlorinated Biphenyl Exposure in the Adult Herring Gull (Larus argentatus) - Sean W. Kennedy; Glen A. Fox; Stephanie P. Jones; Suzanne F. Trudeau (Ecotoxicology, 2003)

Biological Effects of Marine PCB Contamination on Black Guillemot Nestlings at Saglek, Labrador: Liver Biomarkers - Zou Zou A. Kuzyk; Neil M. Burgess; Jason P. Stow; Glen A. Fox (Ecotoxicology, 2003)

Glycoconjugates in the otolithic membrane of herring larvae: a possible framework for encoding the life history recorder in fishes - P. Tytler; C. J. Fox; A. Folkvord (Journal of Fish Biology, 2002)
Glycoconjugates in the inner ear of herring Clupea harengus larvae, investigated by laser confocal and electron microscopy, were located mainly in the gelatinous layer of the otolithic membranes, forming a collar around the proximal surfaces of the otoliths. The site of secretion was located on the surface of the sensory macula, from which a colonnade of glycoconjugate streamers projected through the subcupular region to connect with the gelatinous layer of each otolith. An electron dense component of the outer gelatinous layers, shown by TEM to be closely associated with the sensory kinocilia, suggested that they provided a basis for the streamers and offered a potential role in directing the path of secretion. It is hypothesized that this highly structured glycoconjugate framework could provide a mechanism for localizing and containing ionic and protein gradients previously detected in this vicinity and which are considered to have a key role in driving the differential growth and mineralization of the otoliths.

Genetic diversity within Australian wheat breeding programs based on molecular and pedigree data - G.D. Parker; P.N. Fox; P. Langridge; K. Chalmers; B. Whan; P.F. Ganter (Euphytica, 2002)

Morphological variation of the saker (Falco cherrug) and the implications for conservation - Chris P. Eastham; Mike K. Nicholls; Nick C. Fox (Biodiversity and Conservation, 2002)

Genetic architecture of adaptive differentiation in evolving host races of the soapberry bug, Jadera haematoloma - Scott P. Carroll; Hugh Dingle; Thomas R. Famula; Charles W. Fox (Genetica, 2001)

Inhibition of apoptosis by primary isolates of herpes simplex virus - K. R. Jerome; R. Fox; Z. Chen; P. Sarkar; L. Corey (Archives of Virology, 2001)

Bathymetric Map of the Gorda Plate: Structural and Geomorphological Processes Inferred from Multibeam Surveys - Robert P. Dziak; Christopher G. Fox; Andra M. Bobbitt; Chris Goldfinger (Marine Geophysical Research, 2001)

The effect of the accumulation of disease resistance genes on the long-term association of a global sample of environments for testing spring bread wheat - I. H. DeLacy; S. Rajaram; M. Cooper; P. N. Fox; K. E. Basford (Theoretical and Applied Genetics, 2000)

Recent tectonics of the Blanco Ridge, eastern blanco transform fault zone - Robert P. Dziak; Christopher G. Fox; Robert W. Embley; John L. Nabelek; Jochen Braunmiller; Randolph A. Koski (Marine Geophysical Research, 2000)

Geographic Variation in Hematological Variables in Adult and Prefledgling Herring Gulls ( Larus argentatus ) and Possible Associations with Organochlorine Exposure - K. A. Grasman; P. F. Scanlon; G. A. Fox (Archives of Environmental Contamination and Toxicology, 2000)

Direct and indirect effects of climate change on St John's wort, Hypericum perforatum L. (Hypericaceae) - Laurel R. Fox; Sérvio P. Ribeiro; Valerie K. Brown; Gregory J. Masters; Ian P. Clarke (Oecologia, 1999)

An investigation into the effects of nicotine gum on short-term memory - Sarah Phillips; P. Fox (Psychopharmacology, 1998)

Altered responses to potassium in cerebellar neurons from weaver heterozygote mice - A. P. Fox; S. Dlouhy; B. Ghetti; J. H. Hurley; P. G. P. Nucifora; D. J. Nelson; L. Won; A. Heller (Experimental Brain Research, 1998)

Spatial and Temporal Trends in Organochlorine Contamination and Bill Deformities in Double-Crested Cormorants (Phalacrocorax Auritus) from the Canadian Great Lakes - D.P. Ryckman; D.V. Weseloh; P. Hamr; G.A. Fox; B. Collins; P.J. Ewins; R.J. Norstrom (Environmental Monitoring and Assessment, 1998)

Factors influencing the recovery of submersed macrophytes in four coastal marshes of Lake Ontario - Eric P. S. Sager; Thomas H. Whillans; Michael G. Fox (Wetlands, 1998)

The April 1992 Cape Mendocino Earthquake Sequence: Seismo-Acoustic Analysis Utilizing Fixed Hydrophone Arrays - R. P. Dziak; C. G. Fox; H. Matsumoto; A. E. Schreiner (Marine Geophysical Research, 1997)

Acceleration of cheese ripening - P. F. Fox; J. M. Wallace; S. Morgan; C. M. Lynch; E. J. Niland; J. Tobin (Antonie van Leeuwenhoek, 1996)

Suppression of PLRV Titer in transgenic Russet Burbank and Ranger Russet - Charles R. Brown; Oney P. Smith; V. D. Damsteegt; Ching-Pa Yang; Lee Fox; P. E. Thomas (American Journal of Potato Research, 1995)

Tfm Lac: A second isolation of testicular feminization in mice - J. A. Politch; T. O. Fox; P. Houben; L. Bullock; D. Lovell (Biochemical Genetics, 1988)

Synergistic effects of Aroclor 1254 and mirex on the semen characteristics of American Kestrels - D. M. Bird; P. H. Tucker; Glen A. Fox; P. C. Lagu (Archives of Environmental Contamination and Toxicology, 1983)